Actinomycosis: An infrequent disease in renal transplant recipients?. Issue 6 (11th August 2018) - Rousseau, Celia; Piroth, Lionel; Pernin, Vincent; Cassuto, Elisabeth; Etienne, Isabelle; Jeribi, Ahmed; Kamar, Nassim; Pouteil‐Noble, Claire; Mousson, Christiane
Abstract: Actinomycosis is a rare and heterogeneous infection involving Gram‐positive anaerobic bacteria, which are commensals in the oral cavity and digestive tract. Only four cases of actinomycosis in renal transplant recipients have been reported to date. We performed a retrospective study in French renal transplantation centers to collect data about actinomycosis, patients, and transplantation. Seven cases were reported between 2000 and 2017; mean age was 55.7 years, and prevalence of actinomycosis was 0.02%. Median time between transplantation and infection was 104 months (4‐204 months). Locations of actinomycosis were cervicofacial (n = 2), pulmonary (n = 2), abdominopelvic (n = 2), or cutaneous (n = 1). Two patients (28.5%) had acute kidney injury. Diagnosis was made possible by microbiology (71%) or histopathology (filaments and sulfur granules) (14%) of the infection site. The suspected gate of entry for the infection was dental (57%), abdominal (28.5%) or through the sinuses (14%). All patients were treated with amoxicillin for 30‐200 days (median duration of 115 days), and clavulanic acid was added for 28.5% of cases. Three patients (43%) required surgery. All patients, except one, recovered completely after a few months. Actinomycosis is a rare, slow, progressive disease in French renal transplant recipients. The location and clinical features of this infection are miscellaneous. Global and renal outcomes do not seem to be affected by actinomycosis.